PERANAN KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA SITANGGOR KECAMATAN MUARA KABUPATEN TAPANULI UTARA - Simaremare, Donni; Sianturi, Charles M.; Rajagukguk, Jonson (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study aims to find out how the leadership role of the Sitanggor Village Head, Muara sub-district in increasing community participation in village development. This research is used as information material and can provide useful input for the leadership of the Sitanggor Village Head, Muara District, North Tapanuli Regency. In conducting this research, the researcher used qualitative research methods. The results of this study indicate that the village head must be able and try to build the village according to his vision and mission by involving all elements of the community. The village head must also be able to invite the community to jointly participate in building Sitanggor Village, and in making decisions the village head must implement a deliberation system. In Leadership, it is hoped that the village government and the community can establish good relations and cooperation, with the same goal, namely the success of village development which will have a good impact on improving community welfare. The village head as a leader must be able to carry out coordination and communication, because coordination is absolutely necessary in an organization, because the organization is the executor of the management function of a leader.